The perinatal mental health experiences of black immigrant mothers in the UK: A qualitative systematic review and thematic synthesis - Funmilayo Fabiyi; Zoe Darwin; Rajeeb Kumar Sah; Amanda Firth (PLoS ONE, 2025)
Introduction Mental health difficulties during and after pregnancy are common worldwide. Women from minoritised ethnic communities are disproportionately affected, as are those affected by migration factors. Research typically treats ethnic minority groups as homogenous despite having potentially different needs and experiences. In the UK, Black women face considerable maternal mental health disparities, warranting further attention. Aim To explore and understand the perinatal mental health (PMH) views and experiences of Black immigrant mothers in the UK, the support that was available to them and, perspectives on support received. Methods MAG Online Library, CINAHL, MEDLINE, PsycINFO and Scopus electronic databases were systematically searched. And thematic synthesis was undertaken with all the studies which met the eligibility criteria. Findings Four studies were retrieved, all focusing on postnatal depression. The synthesis generated three themes: i) perceived causes of PMH difficulties, ii) symptoms, signs and impact of PMH difficulties, iii) available support and coping means. Cultural beliefs permeated across all the themes. Conclusion Black immigrant mothers in the UK face challenges such as lack of support, inadequate information, cultural perceptions, and insufficient help from family, community, and healthcare professionals. Further research is needed that extends beyond postnatal depression and includes parent-infant relationships.